A 1.5 V, 0.85-13.35 GHZ MMIC low noise amplifier design using optimization technique - Arjuna, Marzuki; Ali Yeon, Md. Shakaff, Prof. Dr.; Zaliman, Sauli, Prof. Madya (Institution of Electronics and Telecommunication Engineers (IETE), 2010)
Link to publisher's homepage at http://www.jr.ietejournals.org/